Bathymetric distribution of continental slope fishery resources of southern Brazil - Paiva, Melquíades Pinto; Garcez, Danielle Sequeira (Arquivos de Ciências do Mar, 2018)
This paper deals with the bathymetric distribution of continental slope fishery resources of the sou theast Brazil, between latitudes 23'- 26' 5, based on data from bottom liners fisheries (1986- 1995) in depths of 201 - 650 m. The main exploited species were the following, with corresponding participation in total catches: tilefish, Lopholatilus vilarii Ribeiro (59.2%); sandperch, Pseudopercis numida Ribeiro (20.9 %); and snowy grouper, Epinephelus niveatus (Valenciennes) (9.9%). The fish production and fishery effort tended to decrease with the increase of depth, the opposite occurring with the relative abundance (CPUE), at least until the 550 m isobath. As a whole, the CPUE average corresponded to 0.8 kg/hook-day. The three main species were caught until 650 m in depth. The largest catches of tilefish were made between 201 - 300 m in depth and its CPUE tended to increase with the depth increase of fishing grounds- its mean value was 0.5 kg/hookday. The largest catches of sandperch and snowy grouper were made between 201 -250m in depth, and the CPUE mean values were 0.2 and 0.1 kg/hook-day, respectively. Only for the tilefish the data suggest migration to deeper waters, which may occurs during the winter.